Social recognition in the context of Colombia’s post-conflict: Case study of peasant reserve zones - Fajardo, Karen Natalia; Vargas Prieto, Amanda (Cooperativismo & Desarrollo, 2018)
Purpose: The present reflection paper focuses on clarifying how peasant reserve zones (zcr from their initials in Spanish) may be considered a social recognition strategy.Themes: Several aspects must be dealt with through this journey, among them are notions such as justice, recognition and, mainly, Colombian peasant identity.Development: There is evidence that zcr trigger a positive impact on the extent to which they allow peasant’s identity restoration where they establish; this strengthens communities and lets them, take part of, among others, social, economic and environmental decisions.Conclusions: Territory has played a major role in the development of farming and its correspondence with lifestyles and idiosyncrasies of Colombian peasants. This is why the zcr figure involves a social recognition both in cultural and population terms, as well as of their historical significance, which has had an impact on the present.
Keywords: peasants; participation; social recognition; peasant reserve zones (zcr)